Performance of different Gladiolus varieties under the climatic condition of Tista Meander Floodplain in Bangladesh (Progressive Agriculture, 2017)
An experiment was conducted to evaluate 4 cultivars   of Gladiolus BARI Gladiolus 1, BARI Gladiolus 3, BARI Gladiolus 4 and BARI Gladiolus 5at experimental farm, On Farm Research Division, Bangladesh Agricultural Research Institute (BARI), Alamnagar, Rangpur during 2015-2016 and 2016-2017.  The aim of study was to evaluate the adaptability and performance of cultivar under the climatic conditions of Tista Mendar Floodplain Agro Ecological Zone in Bangladesh. Among the varieties BARI Gladiolus-5 performed excellent in terms of spike production in 2015-2016 and BARI Gladiolus-4 performed excellent in terms of spike production in 2016-2017. Among the varieties BARI Gladiolus-4performed excellent in terms of market value in both the years. Maximum spike length was observed in cultivars BARI Gladiolus-4 and BARI Gladiolus-5 remain attractive for longer time. Keeping in view the vegetative and reproductive characteristic cultivars BARI Gladiolus-4 was performed better and recommended for general cultivation. In 2015-2016 the highest gross return (BDT. 1383800 ha-1) as well as gross margin (BDT. 1005144 ha-1) was recorded in BARI Gladiolus-4. In 2016-2017 the highest gross return (BDT. 1318553ha-1) as well as gross margin (BDT. 927153 ha-1) was recorded in BARI Gladiolus-5.The lowest gross return as well as gross margin was obtained from yield BARI Gladiolus-1 in both the yearsTherefore, it could berecommended for commercial cultivation of gladiolusBARI gladiolus 4 and BARI gladiolus 5varietiesare best for Tista Meander Floodplain Agro-Ecological Zone in Bangladesh.Progressive Agriculture 28 (3): 198-203, 2017